Impact of Re-bubbling after Descemet Membrane Endothelial Keratoplasty on Long-term Results. (3rd June 2021) - Gundlach, Enken; Pilger, Daniel; Dietrich-Ntoukas, Tina; Joussen, Antonia M.; Torun, Necip; Maier, Anna-Karina B.
ABSTRACT: Purpose/Aim of the study : Graft detachment after DMEK can be treated easily with an additional air injection – re-bubbling. The aim of our study was to investigate the effect of a re-bubbling on the postoperative outcome. Materials and Methods : In this retrospective, comparative, cohort study we included eyes from patients that underwent DMEK surgery. A graft detachment was diagnosed by slit-lamp examination and OCT scan. All eyes were divided into three groups: no re-bubbling, one re-bubbling, more than one re-bubbling. We analyzed the visual acuity, endothelial cell density and rate of graft failure. Results : In 163 of 463 eyes (35.2%) a re-bubbling was performed (119 eyes 1 re-bubbling, 44 eyes more than one re-bubbling). Visual acuity improved significantly in all groups. After controlling for donor age, reason for surgery, time of cultivation of the graft and preoperative visual acuity, no difference in the visual acuity was seen at any point of follow-up. All patients showed a significant reduction in endothelial cell density 1 month after DMEK. Controlling for donor age, reason for surgery, type of surgery (DMEK-only or DMEK combined with cataract surgery) and the time of cultivation of the graft, the difference in endothelial cell density at 1 month post-surgery between no re-bubbling and one re-bubbling was 157 cells/mm 2 (95% CI 2–310, p = .047) and between no re-bubbling and more than one re-bubbling 504 cells/mm 2 (95% CI 267 − 741, p < .001). The difference in endothelial cell density remained over the course of follow-up. Twenty patients (4.3%) developed a graft failure during postoperative follow-up. Controlling for donor age, reason for surgery and the time of cultivation of the graft, we did not find any difference in the risk of graft failure between re-bubbling categories. Conclusions : Re-bubbling increased the risk for an endothelial cell loss, but did not influence the postoperative visual acuity and the rate of graft failure.